1991
DOI: 10.1111/j.1099-0860.1991.tb00495.x
|View full text |Cite
|
Sign up to set email alerts
|

The abuse of children in out of home care

Abstract: SUMMARY: One of the major paradoxes in child protective services in the United States is that children removed from their homes on protective orders and placed in foster and group care face continued abuse. These children are reported at two to three times the rates of children living with their families. Investigations are performed by the very system that marks placements. In the US, some recommend resolving these problems by withdrawing from the active protection of children in care. Others hold that becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It was this unusual public focus on extra-familial or out-of-home care that led to an initiative by the National Center on Child Abuse and Neglect to fund the first comprehensive national study of ''the state of the art of child protection in child welfare institutions and children's protective agencies in the 48 contiguous states'' (Rindfleisch 1984). Under the leadership of NCCAN, the subsequent eligibility standard from CAPTA legislation of 1984 required that the states not only provide statutory language including out-of-home care as a part of the definition of abuse and neglect (Nunno and Rindfleisch 1991), but also establish ''a statute or administrative procedure requiring that when a report of known or suspected child abuse or neglect involves the acts or omissions of the agency, institution, or facility to which the report would ordinarily be made, a different properly constituted authority must receive and investigate the report and take appropriate protective and corrective action'' [45 CFR § 1340[45 CFR § .14(e), 1985.…”
Section: Child Abuse Prevention and Treatment Actmentioning
confidence: 99%
See 3 more Smart Citations
“…It was this unusual public focus on extra-familial or out-of-home care that led to an initiative by the National Center on Child Abuse and Neglect to fund the first comprehensive national study of ''the state of the art of child protection in child welfare institutions and children's protective agencies in the 48 contiguous states'' (Rindfleisch 1984). Under the leadership of NCCAN, the subsequent eligibility standard from CAPTA legislation of 1984 required that the states not only provide statutory language including out-of-home care as a part of the definition of abuse and neglect (Nunno and Rindfleisch 1991), but also establish ''a statute or administrative procedure requiring that when a report of known or suspected child abuse or neglect involves the acts or omissions of the agency, institution, or facility to which the report would ordinarily be made, a different properly constituted authority must receive and investigate the report and take appropriate protective and corrective action'' [45 CFR § 1340[45 CFR § .14(e), 1985.…”
Section: Child Abuse Prevention and Treatment Actmentioning
confidence: 99%
“…When public attention turned to child abuse and neglect in the 1970s, early estimates suggested that the risk was actually higher in out-ofhome care-placement such as institutions, residential treatment facilities, group homes, foster homes, and day care services-than familial care. Although the information is limited, the risk for child abuse and neglect while in residential or institutional placements has been found to be as great or greater than that of the familial setting (Rindfleisch and Rabb 1984;Rindfleisch and Nunno 1992;Spencer and Knudsen 1992) with estimates given at 2-7 times the rate of familial abuse (Nunno and Rindfleisch 1991;Spencer and Knudsen 1992). These early estimates have been challenged in some recent studies (Tittle et al 2008;Garnier and Poertner 2000;Poertner et al 1999); then again, within categories of out-of-home care, rates for full-time care, as found in institutions, and residential facilities, have been found far higher than those in part-time care such as day care (Spencer and Knudsen 1992).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations